2019
DOI: 10.1101/710970
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comparative assessment of methods for determining adiposity and a model for obesity index

Abstract: 28Background: Obesity is increasingly becoming a pandemic considering the many risks it pose to other

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…Body fat percentage is the percentage of body fat in body weight, which distinguish whether the increase in body weight is caused by muscle or fat increase [ 57 ]. However, BMI evaluates the degree of obesity by the ratio of weight to height that reflect the body’s fat and muscle content to a certain extent [ 58 ]. Previous cross-sectional evidence has suggested that the time spent in sedentary behavior leads to the increase in adiposity, especially the accumulation of abdominal fat [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…Body fat percentage is the percentage of body fat in body weight, which distinguish whether the increase in body weight is caused by muscle or fat increase [ 57 ]. However, BMI evaluates the degree of obesity by the ratio of weight to height that reflect the body’s fat and muscle content to a certain extent [ 58 ]. Previous cross-sectional evidence has suggested that the time spent in sedentary behavior leads to the increase in adiposity, especially the accumulation of abdominal fat [ 59 ].…”
Section: Discussionmentioning
confidence: 99%